Well cementation cement slurry system with low permeability, elasticity and toughness and preparation method of well cementation cement slurry system
By using a low-permeability elastic-tough cementing cement slurry system in shale gas development, combining polypropylene fiber and styrene butadiene rubber latex, the problem of cement ring breakage during fracturing is solved, and the integrity and impact resistance of the wellbore is improved. Performance, achieving more efficient shale gas mining.
Patent Information
- Application Number
- CN202411177480.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing shale gas development technology, cement rings are susceptible to impact damage during fracturing, resulting in the expansion of micro-angle gaps, affecting the integrity and mining efficiency of wellbores, and the existing toughening materials fail to effectively improve impact resistance and protection. Air flow capability.
Using a low-permeability elastic and tough cementing slurry system, by adding polypropylene fiber and styrene butadiene rubber latex to the oil well cement, combined with appropriate component ratios and process flow, the elasticity and impact resistance of the cement slurry are enhanced, and the permeability and Porosity.
It improves the elastic and toughness of the cement ring and long-term sealing ability, reduces permeability and brittleness, enhances impact resistance and anti-air flow ability, and ensures the integrity of the wellbore and mining safety.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of well cementing in shale gas development, and more specifically, relates to a low-permeability elastic-toughness well cementing slurry system and a preparation method thereof. Background Art
[0002] As global energy demand continues to rise, especially in the field of oil and gas resources, my country faces increasingly severe energy security challenges, and the high degree of energy dependence on foreign countries has become an urgent problem to be solved. While actively exploring diversified energy supply paths, shale gas, as a clean and efficient energy resource, is of great significance for alleviating my country's energy pressure and optimizing its energy structure. At present, shale gas development mainly relies on hydraulic fracturing and carbon dioxide fracturing technology. However, these technologies have significant limitations. New technologies such as high-energy gas impact fracturing and methane explosion fracturing use instantaneous high-temperature and high-pressure gas to fracture the target reservoir, which is easy to damage the integrity of the wellbore and seriously affect the efficient development of shale gas fields. Specifically, during the fracturing process, the instantaneous impact force strongly acts on the cement sheath, which is easy to cause it to be crushed by impact. During the loading and unloading process, if the load exceeds the critical strength, the cement sheath will exceed the plastic deformation limit and generate micro-annuli. As the pressure is released, these micro-annuli gradually expand, and the multiple factors such as temperature and chemical erosion increase the risk of cement sheath failure. Mechanical damage and sealing failure of cement sheath directly threaten the integrity of the wellbore, thereby affecting the efficiency and safety of mining operations.
[0003] In the prior art, some prior art did not consider elasticity when using a single material (modified natural rock asphalt) for toughening, which directly led to its insufficient ability to resist deformation, and thus easily induced the formation of micro-annuli. At the same time, the specific impact of the permeability changes of these prior art technologies has yet to be clarified, so their ability to prevent gas cross-flow and prevent imbibition is questionable. In addition, the impact resistance has not been tested and verified. Summary of the invention
[0004] In view of the above defects or improvement requirements of the prior art, the present invention aims to solve the problems in the prior art.
[0005] In order to achieve the above object, according to a first aspect of the present invention, a low-permeability elastic-toughness cementing slurry system is provided, comprising:
[0006] The components are calculated by weight: 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoamer, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer;
[0007] The polypropylene fiber has a length of 8 to 10 mm and an equivalent diameter of 32 to 36 μm;
[0008] The latex is styrene-butadiene rubber latex, the latex is an emulsified polymer, and the spherical polymer particles in the latex exist in the form of an emulsion suspension with a particle size of 0.05 to 0.5 μm;
[0009] The latex stabilizer is a surfactant stabilizer.
[0010] Furthermore, the oil well cement is Grade G high sulfate resistance oil well cement.
[0011] Furthermore, the fluid loss additive is a 2-acrylamide-2-methylpropanesulfonic acid polymer.
[0012] Furthermore, the reinforcing agent is an inorganic reinforcing agent, and the silicon dioxide content in the reinforcing agent is above 92%.
[0013] Furthermore, the expansion agent is an inorganic lattice expansion type treatment agent.
[0014] Furthermore, the retarder is a 2-acrylamide-2-methylpropanesulfonic acid polymer high temperature retarder.
[0015] Furthermore, the dispersant is an acetone-formaldehyde condensation polymer.
[0016] Furthermore, the defoaming agent is a polyether-modified organic silicone emulsion defoaming agent.
[0017] According to a second aspect of the present invention, a method for preparing a low-permeability elastic-toughness cementing slurry system is provided, comprising the following steps:
[0018] S1, weighing raw materials, each component is measured by weight, weighing 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoaming agent, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer;
[0019] S2, preparing dry material, mixing the oil well cement, the reinforcing agent and the expansion agent uniformly to obtain a dry material mixture;
[0020] S3, preparing wet material, first adding defoamer into the water, then sequentially adding fluid loss reducer, retarder, dispersant, latex stabilizer and latex, stirring at a low speed of 4000±200 rpm to form a slurry;
[0021] S4, preparing a cement slurry system, adding the dry material mixture obtained in S1 to the slurry obtained in S2 in batches at room temperature, first stirring at a low speed of 4000±200 rpm and then at a high speed of 12000±500 rpm, and after stirring evenly, adding the dispersed polypropylene fibers in batches to obtain the target cement slurry system.
[0022] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0023] 1. A low-permeability elastic-toughness cementing slurry system of the present invention uses latex and polypropylene fiber, two toughening materials, to compound and toughen the standard cementing slurry, thereby reducing the reduction in strength, improving the density, elasticity, toughness and impact resistance of oil well cement stone, and providing a guarantee for improving the quality of cementing; latex is added to silicate cement, and a flexible polymer film formed at the defects and microcracks of the cement stone disperses the stress inside the cement stone, thereby increasing the deformation ability, impact resistance and anti-gas channeling ability of the cement stone, thereby improving the elasticity and long-term sealing ability of the cement stone; latex will reduce the compressive strength of the cement stone by a small amount, and adding polypropylene fiber can improve the compressive strength of the cement stone. The compounding of the two reduces the elastic modulus while ensuring fluidity and strength, thereby reducing the brittleness of the cement ring.
[0024] 2. The low-permeability elastic-toughness cementing slurry system of the present invention can not only prevent the generation of microcracks by selecting polypropylene fibers of appropriate sizes, but also reduce the porosity of the matrix, thereby improving the anti-seepage ability; adding latex and fiber compounding can reduce the impact of fiber agglomeration, reduce the impact of fiber on the fluidity of cement slurry, and ensure the fluidity requirements of cementing slurry. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] Based on the defects in the existing technology, it is necessary to adopt a high-strength elastic-toughness cement system to effectively prevent mechanical damage to the cement sheath and the generation of micro-annulus, thereby protecting the integrity of the wellbore as a whole. In order to promote new fracturing technology, it is also necessary to solve the problem of cement sheath failure under impact load, improve the elasticity of the cement sheath, reduce cracks caused by impact, and reduce the permeability of the cement sheath to prevent severe imbibition.
[0027] The invention relates to a low-permeability elastic-toughness well cementing slurry system, comprising.
[0028] The components are calculated by weight: 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoamer, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer;
[0029] The polypropylene fiber has a length of 8 to 10 mm and an equivalent diameter of 32 to 36 μm;
[0030] Polypropylene fiber has high strength, good flexibility, easy storage and corrosion resistance, and is a low elastic modulus fiber. Polypropylene fiber is a flexible fiber that can enhance the strength of cement, improve the internal structure of cement matrix, and enhance the stability of cement slurry. Polypropylene fiber can be evenly tailed in cement slurry. This fiber does not participate in the hydration reaction. Its main toughening mechanism includes fiber connection, pull-out energy consumption and crack deflection, which effectively inhibits the formation and expansion of microcracks. Compared with long fibers, short fibers are difficult to produce complex network structures and have little effect on improving the strength of the material. The sliding phenomenon caused by the final shear stress generated by short fibers will have an adverse effect on the "invalid" length of the fiber end. The longer the fiber length, the worse the fluidity. Overlong polypropylene fibers show an uneven dispersion state during the mixing process and are prone to agglomeration, which leads to local defects in the cement matrix and reduces the strength. Fibers that are too short and too long are not suitable for cementing cement slurries that need to meet strength and fluidity requirements. Polypropylene fibers with a length of 8 to 10 mm have high strength, good flexibility, easy storage and corrosion resistance, and are low elastic modulus fibers. This length is between short fiber and long fiber. The effect of this medium fiber on fluidity is less than that of 12mm long fiber, and the effect on strength growth is greater than that of 6mm short fiber. Based on the above factors, the final polypropylene fiber length of 8-10mm is selected.
[0031] Polypropylene fibers with appropriate equivalent diameters ensure sufficient surface area to provide good bonding while also ensuring the strength of the fibers themselves. Although fibers that are too thin have a large surface area, they may break easily during construction due to insufficient strength, affecting the reinforcement effect; while fibers that are too thick may reduce the bonding performance with cement slurry. Appropriate equivalent diameters help the fibers to better penetrate and distribute in cement slurry, reducing the formation of pores and microcracks. Based on the above factors, choosing a diameter of 32 to 36 μm enables the fibers to effectively fill tiny voids during cement slurry solidification, thereby enhancing the density and impermeability of the cementing body.
[0032] In some preferred embodiments, the polypropylene fiber has a length of 9 mm, an equivalent diameter of 34 μm, an initial modulus of 4.0×10 3 MPa, and a tensile strength of 468 MPa.
[0033] The latex is styrene-butadiene rubber latex, the latex is an emulsified polymer, and the spherical polymer particles in the latex exist in the form of an emulsion suspension with a particle size of 0.05 to 0.5 μm;
[0034] The latex can reduce the elastic modulus of cement paste, improve the bonding strength, reduce the permeability of cement paste, and play a good anti-gas channeling effect. Specifically, the styrene-butadiene rubber latex can significantly improve the elasticity and crack resistance of cement slurry, and has good weather resistance and chemical stability, and is suitable for use in complex geological environments. Compared with other latexes, styrene-butadiene rubber latex is more outstanding in enhancing the performance of cement slurry.
[0035] If the spherical polymer particles are too large, the particles will be unevenly distributed in the cement slurry, affecting the performance; if the particle size is too small, the preparation difficulty and cost may be increased, and the latex particles may be excessively aggregated, making it difficult to evenly disperse in the cement slurry, thereby affecting its reinforcing effect. In order to achieve the reinforcing effect of the latex while ensuring the dispersibility, the particle size of the spherical polymer particles in the latex is selected to be between 0.05 and 0.5 μm.
[0036] In some preferred embodiments, the solid content of the latex is 44%, and the selected model is CGR66L, which was purchased from Jingzhou Jiahua Technology Co., Ltd.
[0037] The latex stabilizer is a surfactant stabilizer. Specifically, the latex stabilizer is a mixture mainly composed of surfactants and having emulsification and solubilization functions.
[0038] The main function of the latex stabilizer is to prevent the aggregation and precipitation of latex particles during storage and use, and to maintain the stability and dispersibility of the latex, which is essential for ensuring the uniform distribution of the latex in the cement slurry and giving full play to its reinforcing effect.
[0039] Surfactant stabilizers can significantly reduce the surface tension of liquids, making latex particles more dispersed and stabilized in cement slurry. Compared with other stabilizers, surfactants have better wettability and emulsification, and can more effectively prevent the aggregation and precipitation of latex particles. In addition, surfactants also have good compatibility and stability, and will not adversely affect other components of cement slurry.
[0040] In some preferred embodiments, the latex stabilizer used is model CJ51L, purchased from Jingzhou Jiahua Technology Co., Ltd.
[0041] The oil well cement is G-grade high sulfate resistance oil well cement. In some preferred embodiments, Panlongshan brand G-grade high sulfate resistance (HSR) oil well cement is used.
[0042] The fluid loss additive is a 2-acrylamide-2-methylpropanesulfonic acid (AMPS) polymer. In some preferred embodiments, a fluid loss additive with a model number of CG713L purchased from Tianjin Kelior Engineering Materials Technology Co., Ltd. is used.
[0043] The reinforcing agent is an inorganic reinforcing agent, which is mixed with several inorganic mineral raw materials, inorganic compounds and a small amount of active agents in different proportions, and the main component is silicon dioxide, wherein the silicon dioxide content is above 92%. In some preferred embodiments, the main component of the reinforcing agent (STR) is microsilicon (silicon dioxide).
[0044] The expansion agent is an inorganic lattice expansion treatment agent, which is compounded by inorganic mineral raw materials, non-metals and a small amount of active agents according to different particle gradations. In some preferred embodiments, the expansion agent is an expansion agent BOND.
[0045] The retarder is a 2-acrylamide-2-methylpropanesulfonic acid (AMPS) polymer high temperature retarder. In some preferred embodiments, the retarder model is CH610L, purchased from Tianjin Keliol Engineering Materials Technology Co., Ltd.
[0046] The dispersant is an acetone-formaldehyde polycondensate, which can significantly reduce the viscosity of cementing slurry, increase fluidity, and improve rheological properties. In some preferred embodiments, the dispersant model is CF44L, purchased from Jingzhou Jiahua Technology Co., Ltd.
[0047] The defoamer is a polyether-modified organic silicone emulsion defoamer. In some preferred embodiments, the defoamer model is X66L, purchased from Jingzhou Jiahua Technology Co., Ltd.
[0048] As another aspect of the present invention, it also relates to a method for preparing a low-permeability elastic-toughness cementing slurry system, comprising the following steps:
[0049] S1, weighing raw materials, each component is measured by weight, weighing 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoaming agent, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer;
[0050] S2, preparing dry material, mixing the oil well cement, the reinforcing agent and the expansion agent uniformly to obtain a dry material mixture;
[0051] S3, preparing wet material, first adding defoamer into the water, then sequentially adding fluid loss reducer, retarder, dispersant, latex stabilizer and latex, stirring at a low speed of 4000±200 rpm to form a slurry;
[0052] S4, preparing a cement slurry system, adding the dry material mixture obtained in S1 to the slurry obtained in S2 in batches at room temperature, first stirring at a low speed of 4000±200 rpm and then at a high speed of 12000±500 rpm, and after stirring evenly, adding the dispersed polypropylene fibers in batches to obtain the target cement slurry system.
[0053] Example 1
[0054] 100 parts by weight of grade G cement, 6 parts by weight of reinforcing agent and 2 parts by weight of expansion agent are uniformly mixed to obtain a dry material mixture; 1 part by weight of defoamer is first added to 35.6 parts by weight of water, followed by 4 parts by weight of fluid loss reducer, 0.3 parts by weight of retarder, 0.5 parts by weight of dispersant, 1 part by weight of latex stabilizer and 15 parts by weight of latex are stirred uniformly at a low speed of 4000 rpm to obtain a slurry. The mixed dry material mixture is gradually added to the slurry, stirred at a low speed of 4000 rpm first and then at a high speed of 12000 rpm, and after being uniformly stirred, 0.5 parts by weight of dispersed polypropylene fiber is gradually added to obtain a low-permeability elastic toughness cementing slurry system.
[0055] Comparative Example 1
[0056] 100 parts by weight of grade G cement, 6 parts by weight of a reinforcing agent and 2 parts by weight of an expanding agent are uniformly mixed to obtain a dry material mixture; 1 part by weight of a defoamer is first added to 35.6 parts by weight of water, followed by 4 parts by weight of a fluid loss reducer, 0.3 parts by weight of a retarder and 0.5 parts by weight of a dispersant, and the mixture is stirred uniformly at a low speed of 4000 rpm to prepare a slurry; the mixed dry material mixture is gradually added to the slurry, and stirred uniformly at a low speed of 4000 rpm and then at a high speed of 12000 rpm to obtain a basic cementing cement slurry system.
[0057] Compared with Example 1, Comparative Example 1 did not add polypropylene fiber, latex, or latex stabilizer.
[0058] The standard samples prepared by Example 1 and Comparative Example 1 were subjected to uniaxial compression and triaxial compression tests, the permeability test was conducted by pulse attenuation method, and the dynamic impact test was conducted by Hopkinson bar. The static test results of cementing stone of the example and comparative example samples are as follows:
[0059]
[0060] The data show that the compressive strength of Example 1 is slightly lower than that of Comparative Example 1. The elastic modulus decreases by about 15%, the Poisson's ratio increases by 34.4%, the internal friction angle decreases by about 35%, and the cohesion remains almost unchanged. That is, the elastic modulus of Example 1 decreases, its elastic deformation capacity increases, and its toughness increases. The reduction in stiffness reduces the risk of micropore formation and improves the integrity of the cement ring. A higher Poisson's ratio indicates that the material is not prone to lateral deformation when subjected to forces in other directions, which enhances the resistance of the cement casing to tensile and shear forces. Therefore, increasing toughness and elasticity by incorporating latex, fiber and latex stabilizer into the cement slurry system is crucial to reducing crack formation and preventing cement casing from breaking during perforation and fracturing. This improvement is crucial to maintaining the integrity of the cement casing. By analyzing the performance test results of Example 1 and Comparative Example 1, it can be seen that the compressive strength of the example is slightly reduced, and the reduction in the elastic modulus means that the brittleness is reduced, the impact resistance is improved, and the toughness is increased.
[0061] Permeability is a key parameter for evaluating the sealing performance and durability of cement paste. The measured permeability of Comparative Example 1 was 1252.4 mD, while the permeability of Example 1 was 90.8 mD. The test results showed that the permeability was reduced by 99.28%. The latex polymer filled the pores and enhanced the density of the cement paste, thereby reducing its permeability and improving its resistance to gas channeling.
[0062] The cementing cement kinetic test results of Example 1 and Comparative Example 1 are as follows:
[0063]
[0064] At the peak stress of each test, the peak strain of Example 1 is higher than that of Comparative Example 1. As the peak strain rate increases, Example 1 shows a higher peak strain and smaller damage extension. Example 1 always has a higher dynamic enhancement factor DIF at the same strain rate, can withstand higher peak pressure at high strain rates, and has improved ductility and impact resistance. Example 1 is more suitable for bearing impact loads than Comparative Example 1.
[0065] Example 1 exhibits superior performance in both static and dynamic mechanical properties. Its higher compressive strength, elastic modulus and peak strain indicate that it has better deformation capacity and energy absorption capacity when subjected to high strain rate loads. This enables Example 1 to more effectively maintain structural integrity and prevent cement casing damage during wellbore operations such as fracturing and drilling.
[0066] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A low permeability elastic toughness cementing slurry system, characterized in that: include: The components are calculated by weight: 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoamer, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer; The polypropylene fiber has a length of 8 to 10 mm and an equivalent diameter of 32 to 36 μm; The latex is styrene-butadiene rubber latex, the latex is an emulsified polymer, and the spherical polymer particles in the latex exist in the form of an emulsion suspension with a particle size of 0.05 to 0.5 μm; The latex stabilizer is a surfactant stabilizer.
2. The low permeability elastic toughness cementing slurry system according to claim 1, characterized in that: The oil well cement is a G-grade high sulfate resistance oil well cement.
3. The low permeability elastic toughness cementing slurry system according to claim 1, characterized in that: The fluid loss reducer is a 2-acrylamide-2-methylpropanesulfonic acid polymer.
4. The low permeability elastic toughness cementing slurry system according to claim 1, characterized in that: The reinforcing agent is an inorganic reinforcing agent, and the silicon dioxide content in the reinforcing agent is above 92%.
5. The low permeability elastic toughness cementing slurry system according to claim 1, characterized in that: The expansion agent is an inorganic lattice expansion type treatment agent.
6. The low-permeability elastic-toughness cementing slurry system according to claim 1, characterized in that: The retarder is a 2-acrylamide-2-methylpropane sulfonic acid polymer high temperature retarder.
7. The low-permeability elastic-toughness cementing slurry system according to claim 1, characterized in that: The dispersant is an acetone-formaldehyde condensate.
8. The low permeability elastic toughness cementing slurry system according to claim 1, characterized in that: The defoamer is a polyether-modified organic silicone emulsion defoamer.
9. A method for preparing a low-permeability elastic-toughness cementing slurry system according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, weighing raw materials, each component is measured by weight, weighing 100 parts of oil well cement, 35.6 parts of water, 4-6 parts of fluid loss reducer, 4-6 parts of reinforcing agent, 2-3 parts of expansion agent, 0.3-0.5 parts of retarder, 0.5-1 parts of dispersant, 0.5-1 parts of defoaming agent, 0.5-1 parts of polypropylene fiber, 10-15 parts of latex and 0.5-1 parts of latex stabilizer; S2, preparing dry material, mixing the oil well cement, the reinforcing agent and the expansion agent uniformly to obtain a dry material mixture; S3, preparing wet material, first adding defoamer into the water, then sequentially adding fluid loss reducer, retarder, dispersant, latex stabilizer and latex, stirring at a low speed of 4000±200 rpm to form a slurry; S4, preparing a cement slurry system, adding the dry material mixture obtained in S1 to the slurry obtained in S2 in batches at room temperature, first stirring at a low speed of 4000±200 rpm and then at a high speed of 12000±500 rpm, and after stirring evenly, adding the dispersed polypropylene fibers in batches to obtain the target cement slurry system.